Occurrence and mobility of major and trace elements in groundwater from pristine volcanic aquifers in Jeju Island, Korea. (February 2016) - Koh, Dong-Chan; Chae, Gi-Tak; Ryu, Jong-Sik; Lee, Seung-Gu; Ko, Kyung-Seok
Abstract: Major and trace elements in groundwater from basaltic aquifers in pristine conditions were investigated in a volcanic island to evaluate sources, sinks, and mobility of elements over a wide range of mineralization conditions with total dissolved solids from 50 mg/L to 3400 mg/L. Groundwater was highly undersaturated with respect to primary silicate minerals, indicating that dissolution of basaltic rocks may continue under conditions with precipitation of calcite and secondary silicates. Evolution of B/Cl ratio in groundwater from marine aerosols to basaltic rocks showed that the ratio could be used as a conservative tracer for interactions between water and basaltic rocks. Relative mobility (RM) of elements calculated using the concentrations of elements in the local basaltic rocks and those in groundwater showed that mobility decreased in the order of B > Rb > Na > K > Mg > Ca > Mo > V > Si > Sr > Sc > P > U > Zn > Pb > Cr > Cu > Ba > Ni > Ti > (Mn, Al, Fe, Co, Th) indicating that oxyanion-forming elements and alkali metals had the highest mobility. Compared to average RM, V had decreased mobility, and Fe and Mn had increased mobility in anoxic groundwater while V, Mo, and U had higher mobility in oxic-alkaline water. The sources of V, Cr, Cu, and Zn in rocks were estimated using the partition coefficients between minerals and basaltic melt, and the disparity between sources and mobility indicated that sinks are more important for controlling the concentrations of these elements in groundwater than the contents in the rocks. Principal component analysis (PCA) of hydrogeochemical parameters in groundwater produced three principal components (PC) which represent dissolution of basaltic rocks without significant attenuation of released solutes, higher degree of water–rock interactions resulting in oxic-alkaline conditions, and attenuation of Zn and Cu in higher pH, respectively. Spatial distribution of PCs revealed that groundwater with elevated concentrations of mobile elements was concentrated in the southwestern area and that concentrations of V and Cr were more scattered, which is likely to be controlled by pH and redox states of groundwater as well as degree of water–rock interactions. Highlights: We investigate hydrogeochemistry of pristine basaltic aquifers. Groundwater is largely undersaturated with primary silicate minerals. We evaluate relative mobility of major and trace elements in groundwater. V, U, Zn, and Cr show higher variability in their occurrence and mobility. Water–rock interaction, pH, and redox control mobility of elements in groundwater.